Development and Internal Validation of a Clinical Risk Score for Hypovitaminosis D in Italian Adults Aged ≥50 Years Attending Osteoporosis and Metabolic Bone Disease Centers - Ranuccio Nuti; Luigi Gennari; Bruno Frediani; Stefano Gonnelli; Daniela Merlotti; Carla Caffarelli; Giovanni Minisola; Antonino Catalano; Nazzarena Malavolta; Monica Pinto; Giulia Letizia Mauro; Vito Mascolo; et al. (Nutrients, 2026)
Background/Objectives: Hypovitaminosis-D is a highly prevalent condition worldwide, associated with adverse skeletal and extra-skeletal outcomes. Increasing demand for serum 25-hydroxyvitamin D (25(OH)D) testing points toward the need for simple tools to identify individuals at risk and optimize laboratory use. We aimed to develop and validate a clinical risk score for predicting hypovitaminosis-D based on easily assessable risk factors. Methods: This cross-sectional study included 1408 adults aged ≥50 years (1286 women and 122 men) attending centers across Italy dedicated to osteoporosis and metabolic bone diseases. Demographic, clinical, lifestyle, and dietary data were collected through a standardized questionnaire. Overall, 1147 subjects (81.5%) were receiving cholecalciferol supplementation. Univariable and multivariable logistic regression analyses identified predictors of 25(OH)D < 20 ng/mL (primary outcome) and